Assessing the E-learning Readiness of Universities in Developing Countries and Expected Obstacles - Ate, Abdelrahim; Zaineldeenc, Samar; Zhaohui, Cai; Zhao, Yan (UI Scholars Hub, 2021)
To benefit from electronic learning (E-learning), organizations should execute considerable upfront analysis to ascertain their E-learning readiness. Studies have demonstrated a range of models that have been adapted, but they are used in developed counties for whom E-learning readiness is elevated. Thus, these models are not valid in growing countries, such as Sudan. Based on a modified model, this research was performed descriptively by applying a questionnaire-based survey method to assess the level of Sudan universities’ readiness in the employment of the E-learning system. This modified model includes social support, technology readiness, attitude toward E-learning, acceptance of E-learning, and individual learners. Furthermore, the adoption and implementation of E-learning involve numerous challenges and constraints. Therefore, in this study, the challenges that could be faced in applying E-learning in Sudan from students’ perspectives are investigated. The results show that the most prepared factor is individual learners at Sudanese universities. However, this factor still needs a few improvements for E-learning with an overall mean (3.59). Given that the learners are willing to collaborate and share information and knowledge, they can manage time for their learning, and they are also motivated and enthusiastic about using computers. Moreover, attitude toward E-learning is the least prepared factor among all factors (mean = 3.16), which means that this factor is not ready and needs some work. The study recognizes serious barriers that constrain the effective incorporation of E-learning in higher education institutes (HEIs) in developing countries.